In the Process of Social Relations Characteristics, Methods and Development Mechanisms of Rational and Irrational Thinking (Eurasian Journal of Humanities and Social Sciences, 2022)
This article presents a theoretical analysis of the characteristics, methods and mechanisms of development of rational and irrational thinking in the process of social relations, as well as analysis of problems, synthesis of details, and comparison of facts in rational thinking